The Role of Human Resources Management in achieving competitive advantage based on the resource – Efficiency model “The japanese experience is a model” - زياني خولة; بوغليطة الهام (Finance and Business Economies Review, 2020)
The strongest factor for the profitability of the institution relates to its ability to optimally use its internal resources and to direct attention to the approach based on resources and competencies, which is summarized in that resources are all that generate an outflow from their exploitation, while competencies merge two dimensions, namely the human dimension and the strategic dimension, where successful institutions are the ones that possess competencies. Humanity with high capabilities, this is what made many Maha seek to possess it and work to raise its innovative capabilities through its continuous development, which makes it an important source for its competitive advantage. The Japanese School of Human Resources Management and Development is one of the most important global models that must be emulated. It relies in its strategies for developing human resources on a number of elements, the most important of which is participatory management..